Hubungan Antara Situasi Akademik Dengan Self-Regulated Learning Pada Mahasiswa Bimbingan Konseling Pendidikan Islam - Rahmad Yazidsyah; Ade Chita Putri Harahap (Jurnal Bimbingan dan Konseling Ar-Rahman, 2023)
This study aims to find out the relationship between the academic situation and the self-regulated learning of Islamic Education Counseling Guidance students. Self-regulated learning includes a person's expertise in effectively managing one's own learning experiences in various ways to achieve the best learning outcomes. In this study the research method used is descriptive quantitative research method. The subjects in this study were active students in semester 5 of 2020 who were enrolled in the Islamic Education Counseling Guidance Study Program, State Islamic University of North Sumatra. Sample data collection was carried out randomly (random sampling) with a total sample of 132 people. Research data was collected using a questionnaire or questionnaire from two variables, namely the academic situation variable and the self-regulated learning variable using a Likert scale. The collected data were analyzed using a Simple Linear Regression test. From the results of the research that has been done, it is found that the R value of 0.517 indicates the magnitude of the correlation coefficient, so that it can be concluded that there is a positive and significant relationship between the academic situation and self-regulated learning. For subsequent research, it is hoped that it can develop related to how to increase students' understanding of self-regulated learning. ____________________________________________________________ Penelitian ini memiliki tujuan untuk mengetahui bagaimana hubungan antara situasi akademik dengan self-regulated learning mahasiswa Bimbingan Konseling Pendidikan Islam. Self-regulated learning termasuk keahlian seseorang secara efektif untuk mengelola pengalaman belajar diri sendiri dengan berbagai cara untuk meraih hasil belajar yang terbaik. Dalam penelitian ini metode penelitian yang dipakai yaitu metode penelitian kuantitatif deskriptif. Subjek pada  penelitian ini adalah mahasiswa aktif semester 5 stambuk 2020 yang terdaftar di Program Studi Bimbingan Konseling Pendidikan Islam, Universitas Islam Negeri Sumatera Utara. Pengambilan data sampel dilakukan secara acak (random sampling) dengan total sampel 132 orang. Data penelitian dikumpulkan menggunakan angket atau kuesioner dari dua variabel yaitu variabel situasi akademik dan variabel self-regulated learning menggunakan skala likert.  Data yang dikumpulkan dianalisis menggunkan uji Regresi Linear Sederhana. Dari hasil penelitian yang telah dilakukan di dapatkan bahwa nilai R sebesar 0,517 menunjukkan besarnya koefisien korelasi, sehingga bisa simpulkan terdapat hubungan positif dan signifikan antara situasi akademik dengan self-regulated learning. Untuk penelitian berikutnya diharapkan agar dapat mengembangkan terkait bagaimana meningkatkan pemahaman mahasiswa mengenai self-regulated learning.